RPS lineman conquers many challenges - Ferrendelli, Betta (Raton Range Raton, New Mexico, 1992)
Newspaper article on Robert Lucero City of Raton employee. Lineman for Raton Public Service Company.
Master list item #: 12
File location is in the Raton file Cabinet
Keywords: Lucero, Robert; Raton Public Service Company; Local History; Biography; Lineman; Electic Company; Power Plant; Raton, New Mexico